EXPERT COUNCIL "FEDERAL CLINICAL RECOMMENDATIONS ON VACCINAL PREVENTION OF THE DISEASES CAUSED BY HUMAN PAPILLOMA VIRUS" - Article Editorial (Union of pediatricians of Russia, 2016)
31 октября 2015 г. на базе Научного центра здоровья детей (Москва) состоялся Совет экспертов по разработке клинических рекомендаций по вакцинопрофилактике заболеваний, вызванных вирусом папилломы человека.